2006
DOI: 10.1111/j.1469-1809.2006.00278.x
|View full text |Cite
|
Sign up to set email alerts
|

Association Study of G Protein‐Coupled Receptor Kinase 4 Gene Variants with Essential Hypertension in Northern Han Chinese

Abstract: SummaryTo investigate the association between polymorphisms in the G protein-coupled receptor kinase 4 gene (GRK4) (R65L, A142V and A486V ) and essential hypertension in northern Han Chinese, we conducted a case-control study consisting of 503 individuals with essential hypertension (HT) and 490 age-, gender-, and area-matched normotensive (NT) controls. The three GRK4 variants were genotyped by PCR-RFLP analysis. Both haplotype and single locus analysis were used to process the genotyping data. The A486 allel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…An Australian group confirmed the association between the Val142 GRK4 polymorphism and essential hypertension in a case-control study of 168 Caucasian hypertensive subjects and 312 normotensive controls (296). A case control study of ϳ1,000 Chinese showed an association between the GRK4 position 486 polymorphism and essential hypertension (110,326). In contrast, a study from the Netherlands found no association between the GRK4 Ala142Val polymorphism and blood pressure or renal sodium excretion (299).…”
Section: Grk Polymorphismsmentioning
confidence: 83%
“…An Australian group confirmed the association between the Val142 GRK4 polymorphism and essential hypertension in a case-control study of 168 Caucasian hypertensive subjects and 312 normotensive controls (296). A case control study of ϳ1,000 Chinese showed an association between the GRK4 position 486 polymorphism and essential hypertension (110,326). In contrast, a study from the Netherlands found no association between the GRK4 Ala142Val polymorphism and blood pressure or renal sodium excretion (299).…”
Section: Grk Polymorphismsmentioning
confidence: 83%
“…Furthermore, GRK4 single nucleotide polymorphisms have been previously reported and include R65L, A142V, and A486V. GRK4-A486V has been associated with hypertension in Italian patients (15), in Chinese patients (267), and in an Australian cohort of patients (234). Although in these three studies no association between hypertension and GRK4-R65L or GRK4-A142V variant was seen, increasing copies of GRK4-R65L and GRK4-A142V were associated with reduced atenolol-induced diastolic blood pressure lowering (256).…”
Section: B Grk4 and Grk6 In Hypertensionmentioning
confidence: 99%
“…43 In another study, GRK4 486V is associated with hypertension in Italian subjects, 44 reminiscent of the phenotype of the human GRK4 486V transgenic mice. 36 In a study of northern Han Chinese subjects, the GRK4 65L, 142V, and A486 haplotypes are associated with a 6-fold higher risk of systolic and diastolic hypertension 45 (Table 2). In another report of the same Han Chinese data from the same group, the A486V polymorphism is also shown to be associated with hypertension, but the allele that increased the risk is 486V.…”
Section: Grk4 Polymorphisms and Hypertensionmentioning
confidence: 99%